The nucleation of the Izmit and Düzce earthquakes: some mechanical logic on where and how ruptures began. Issue 3 (29th January 2021) - Bouchon, Michel; Karabulut, Hayrullah; Aktar, Mustafa; Özalaybey, Serdar; Schmittbuhl, Jean; Bouin, Marie-Paule; Marsan, David
SUMMARY: In spite of growing evidence that many earthquakes are preceded by increased seismic activity, the nature of this activity is still poorly understood. Is it the result of a mostly random process related to the natural tendency of seismic events to cluster in time and space, in which case there is little hope to ever predict earthquakes? Or is it the sign that a physical process that will lead to the impending rupture has begun, in which case we should attempt to identify this process. With this aim we take a further look at the nucleation of two of the best recorded and documented strike-slip earthquakes to date, the 1999 Izmit and Düzce earthquakes which ruptured the North Anatolian Fault over ∼200 km. We show the existence of a remarkable mechanical logic linking together nucleation characteristics, stress loading, fault geometry and rupture speed. In both earthquakes the observations point to slow aseismic slip occurring near the ductile-to-brittle transition zone as the motor of their nucleation.